Rock Characteristics as The Basis of Aquifer Determination In Cianjur Sub-Watershed, Cugenang District, Cianjur Regency, West Java Province - Husaeni, Ahmad; Listiawan, Yudhi; Fachrudin, Kurnia Arfiansyah; Iskandarsyah, Teuku Yan Waliana Muda (Journal of Geological Sciences and Applied Geology, 2021)
Based on Presidential Decree Number 12 of 2012, this research area is part of the Upstream Citarum watershed and part of the Citarum River Basin. The boundary of this research area is the Cianjur Sub-watershed which has an area of approximately 41.0 km2. The research area is the eastern part of Mount Gede. This study aimed to determine the characteristics of the lithology as the basis of aquifer determination that composed the research area based on the results of surface geological mapping and supported by petrographic analysis. This research used a method split into several stages, namely the stages of fieldwork, rock sampling, and laboratory analysis. At the fieldwork stage, geological mapping of the surface was carried out by observing rock outcrops in the research area. At the sampling stage, it is done by taking rock samples representing each rock unit in the research area. As for the last stage, laboratory analysis is performed using the petrographic analysis method, namely the analysis of thin sections on rock samples to observe each of the mineral contained and porosity characteristics in the rock samples. The results of the thin section analysis are then compared with the existing classifications. Based on the results of the analysis, the research area is composed of igneous rocks, volcanic rocks, and pyroclastic rocks which are divided into three (3) units, namely the Volcanic Breccia Unit (SBv), Volcanic Tuff Unit (STv), and Volcanic Lava Unit (SLv). Based on these three units of lithology, SBv which is a unit of volcanic breccia is an aquifer